Governing finance in Europe: discussion and conclusion (2020)
In this book we have raised the question of whether and why the governance of financial markets has led to a centralisation, decentralisation or fragmentation of regulatory structures in Europe. In the theory chapter we developed hypothetical answers to this question from four research perspectives: European legislation in the context of international agreements; international competition between regulatory powers; the interaction between private self-regulation and public regulation; and technological (digital) innovation of financial instruments.